Coopetition in New Product Development Alliances: Advantages and Tensions for Incremental and Radical Innovation. (26th January 2017) - Bouncken, Ricarda B.; Fredrich, Viktor; Ritala, Paavo; Kraus, Sascha
Abstract: Coopetition (collaboration between competitors) can facilitate product innovation, but there is still debate about how it is suited to radical or incremental innovation. This paper argues that the early and later phases of coopetitive new product development (NPD) pose different benefits and risks for the innovation types. Building on the tensions approach to value creation and appropriation, we develop a series of hypotheses on the role of coopetition in NPD alliances and focal firm's innovation output. The hypotheses are tested on a quantitative data set of 1049 NPD alliances in the German medical and machinery sectors. The results show that, while coopetition is advantageous for incremental innovation in both pre‐launch and launch phases, radical innovation benefits from coopetition in the launch phase only.